Characterization of trehalolipid biosurfactant produced by the novel marine strain Rhodococcus sp. SP1d and its potential for environmental applications - Marco Andreolli; Valeria Villanova; Serena Zanzoni; Mariapina D’Onofrio; Giovanni Vallini; Nicola Secchi; Silvia Lampis (Microbial Cell Factories, 2023)
Abstract Background Biosurfactants are surface-active compounds with environmental and industrial applications. These molecules show higher biocompatibility, stability and efficiency compared to synthetic surfactants. On the other hand, biosurfactants are not cost-competitive to their chemical counterparts. Cost effective technology such as the use of low-cost substrates is a promising approach aimed at reducing the production cost. This study aimed to evaluate the biosurfactant production and activity by the novel strain Rhodococcus sp. SP1d by using different growth substrates. Therefore, to exploit the biosurfactant synthesized by SP1d for environmental applications, the effect of this compound on the bacteria biofilm formation was evaluated. Eventually, for a possible bioremediation application, the biosurfactant properties and its chemical characteristics were investigated using diesel as source of carbon. Results Rhodococcus sp. SP1d evidence the highest similarity to Rhodococcus globerulus DSM 43954T and the ability to biosynthesize surfactants using a wide range of substrates such as exhausted vegetable oil, mineral oil, butter, n-hexadecane, and diesel. The maximum production of crude biosurfactant after 10 days of incubation was reached on n-hexadecane and diesel with a final yield of 2.38 ± 0.51 and 1.86 ± 0.31 g L− 1 respectively. Biosurfactants produced by SP1d enhanced the biofilm production of P. protegens MP12. Moreover, the results showed the ability of SP1d to produce biosurfactants on diesel even when grown at 10 and 18 °C. The biosurfactant activity was maintained over a wide range of NaCl concentration, pH, and temperature. A concentration of 1000 mg L− 1 of the crude biosurfactant showed an emulsification activity of 55% towards both xylene and olive oil and a reduction of 25.0 mN m− 1 of surface tension of water. Eventually, nuclear magnetic resonance spectroscopy indicated that the biosurfactant is formed by trehalolipids. Conclusions The use of low-cost substrates such as exhausted oils and waste butter reduce both the costs of biosurfactant synthesis and the environmental pollution due to the inappropriate disposal of these residues. High production yields, stability and emulsification properties using diesel and n-hexadecane as substrates, make the biosurfactant produced by SP1d a sustainable biocompound for bioremediation purpose. Eventually, the purified biosurfactant improved the biofilm formation of the fungal antagonistic strain P. protegens MP12, and thus seem to be exploitable to increase the adherence and colonization of plant surfaces by this antagonistic strain and possibly enhance antifungal activity.